Phenylazide Hybrid‐Silica – Polarization Platform for Dynamic Nuclear Polarization at Cryogenic Temperatures. Issue 1 (22nd December 2016) - Grüning, Wolfram R.; Bieringer, Harald; Schwarzwälder, Martin; Gajan, David; Bornet, Aurélien; Vuichoud, Basile; Milani, Jonas; Baudouin, David; Veyre, Laurent; Lesage, Anne; Jannin, Sami; Bodenhausen, Geoffrey; et al.
Abstract : Hyperpolarization of NMR‐active nuclei is key to gather high quality spectra of rare species and insensitive isotopes. We have recently established that silica‐based materials containing regularly distributed nitroxyl radicals connected to the silica matrix by flexible linkers can serve as promising polarization matrices for dynamic nuclear polarization (DNP). Here we investigate the influence of the linker on the efficiency of the polarization. The materials were fully characterized and exhibit high surface areas and narrow pore size distributions with a tunable amount of phenyl azide groups over a broad range of concentrations. The phenyl azide groups can be easily functionalized via a two‐step procedure with 4‐carboxy‐2, 2, 6, 6‐tetramethyl‐1‐oxylpiperidine (TEMPO) to give polarizing matrices with controllable radical content. The DNP efficiency was found to be similar as in materials with flexible linkers, both for magic angle spinning at 105 K and dissolution DNP at 4 K. Abstract :